ANALYSIS OF THE CAUSES OF THE 1997 MONETARY CRISIS AND ITS INFLUENCE ON BANKING POLICY IN INDONESIA - Hanif, Ahmad (Jurnal Keuangan dan Perbankan (KEBAN), 2024)
There is no doubt that the US financial crisis has had an impact on the global financial landscape. Countries in the European region such as Iceland, the Netherlands, Russia, the United Kingdom, Germany, France, as well as those in the Asia-Pacific region, such as Taiwan, China, Singapore, the Philippines, Australia, and Japan were affected by the crisis. This study uses a descriptive analysis method, This is to look into certain situations and conditions, with the findings being reported as research reports. This research investigates the circumstances, conditions and results. The results are presented in the research report as is. Secondary data taken from Bank Indonesia (BI), Central Statistics Agency (BPS), Ministry of Trade, and Indonesian Bank websites were used to form opinion groups from each economic expert during the 1997-1998 crisis. The contributing factors are economic growth, money supply (JUB), interest rates, exchange rates, Debt Service Ratio (DSR), Gross Domestic Gross (GDB), Balance of Payment (BOP), and Inflation. In order to combat inflation brought on by the rupiah's depreciation versus the dollar, Bank Indonesia had to raise the BI rate as a result of the financial crisis. Conventional bank interest rates increased dramatically in response to the rise in the BI rate. However, this increase in interest rates does not affect Islamic banks directly. The economic crisis is caused by unstable markets, has an up-and-down conjuncture, therefore for better results the Government should intervene in the market through its policies.